Unicornuate Uterus with Non-Communicating Rudimentary Uterine Horn on MRI: A Case Report - Haroon, Dr Quratulain; Altaf, Dr Raisa; Nasir, Dr Sadaf; Ansari, Dr Awais (International Journal of Innovative Research in Medical Science, 2025)
Uterine anomalies resulting from abnormal embryologic development of the Mullerian ducts are often detected incidentally on imaging for other indications. This case report presents the finding of a non-communicating rudimentary uterine horn on MRI in a 31-year-old married female, along with a discussion of the typical imaging features, clinical implications, and management considerations for this rare anomaly. This report highlights the crucial role of imaging in diagnosing Mullerian duct abnormalities.